The Greatest Threat : Iraq, Weapons of Mass Destruction, and the Crisis of Global Security - Butler, Richard (New York PublicAffairs, 2001)
This book is a record of the incomplete attempt by the United Nations Security Council to disarm Saddam Hussein of his weapons of mass destruction in the aftermath of the 1991 Persian Gulf War.
Include Notes on Sources and Index
Keywords: United Nations - Special Commission on Iraq -- Iraq - Military policy -- Weapons of mass destruction -- Iraq